Dynamic Modeling and Response Characteristics Analysis in High-Temperature Melting and Rolling Process of Laminated Steel - Xin, Yanli; Gao, Zhiying; Wang, Xiaoyong; Zhang, Qingdong; Zhou, Xiaomin (Journal of Engineering and Technological Sciences, 2025)
High-temperature melting and rolling is the key process of laminated steel production. The dynamic fluctuation of the rolling force during the film covering process causes an alternating effect of positive and negative pressures in the film covering area. The roll vibration causes the film to vibrate up and down, leading to the generation and intensification of bubbles, which seriously affects the product quality. In this study, considering the nonlinear stiffness characteristics of a polyethylene terephthalate (PET) film under unidirectional compression in the roll gap, a melting and rolling dynamic model with the structure and process coupled was established. Taking the melting layer and the rolling force as intermediate variables, process parameters such as strip temperature and rolling speed were introduced into the dynamic model, and the influence of process parameters on the film filling rate and the roll vibration displacement response was discussed. Considering the external disturbances of the strip thickness difference and the roll eccentricity, the dynamic characteristics of the rolling force, roll displacement, and filling rate under different strip temperatures and rolling speeds were analysed. The research results indicated that with an increase in the rolling speed and a decrease in the strip temperature, the filling rate, roll displacement, and rolling force increased, affecting the quality of laminated steel. Therefore, modeling the dynamic mechanism and studying the dynamic rolling force characteristics of the high-temperature melting and rolling process of laminated steel can provide a theoretical basis for controlling and optimizing of the film covering process.